Airline Delay Propagation: A Simple Method for Measuring Its Extent and Determinants - Jan K. Brueckner; Achim I. Czerny; Alberto A. Gaggero (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper offers a simple approach for identifying propagated departure delays and measuring their contribution to arrival delays. Under our approach, a propagated departure delay occurs when the arrival delay of the inbound flight exceeds the subsequent flight's ground buffer. The size (or frequency) of such propagated delays relative to the size (or frequency) of arrival delays then measures the contribution of propagated delays to late arrivals. This approach differs from earlier attempts to quantify the contribution of delay propagation since it focuses on an individual flight and its immediate predecessor, without attempting to trace the sources of delay propagation back through the entire sequence of prior flights. The paper's empirical results show that the contribution of propagated departure delays to arrival delays depends on several key determinants.
Keywords: L93; R41; 330